Effect of technology transfer through frontline demonstrations on yield and economics of safflower in scarcity area of Western Maharashtra: Effect of technology transfer through frontline demonstrations on yield and economics of safflower in scarcity area of Western Maharashtra - V D SHENDE; SV KHADTARE; S K SHINDE (Journal of Oilseeds Research, 2020)
A total of 790 frontline demonstrations were conducted on farmers’ field during last three decades (1987-88 to2018-19) in scarcity zone of Maharashtra state. The components viz., whole package, thinning, improved variety,recommended dose of fertilizers, plant protection measures and intercropping were tested with local package ofpractices. The intercropping of gram and safflower (6:3) and use of RDF under rain fed conditions were the mosteconomical component which increased monetary returns by 46 and 40 per cent over local practice. The results also revealed that awareness in respect of use of improved varieties, balanced fertilization, IPM module adoption and précise use of component technologies brought a significant change in their livelihood through additional income.